Trad wife : a novel - Schaefer, Saratoga (Crooked Lane Books, 2026)
When Camille Deming isn't cooking, cleaning, or homesteading in her picture-perfect country farmhouse, she's posting about her tradwife lifestyle for her online followers. She takes inspiration from other tradwives on social media, aspiring to be like them, but Camille's missing a key component: a baby. And contrary to what she posts online, things with her husband, Graham, have been strained. Pressured by her eager followers, Camille fears that without a baby, her relationship will suffer and her social media will never grow out of its infancy. When Camille discovers a mysterious, decrepit well in the wheatfield behind her house, she makes a wish for a baby. Afterward, she has unsettling experiences that she convinces herself are angelic in nature, and when she's visited one night by a strange creature, her wish comes true. Camille's pregnancy announcement gets more engagement than anything she's ever posted--so what if Graham's reaction is lukewarm? Camille's life is finally falling into place. Never mind that her pregnancy is developing freakishly rapidly and she's suddenly craving raw meat. Being a traditional wife is worth it.